2001
DOI: 10.1111/j.1651-2227.2001.tb01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmune bovine colostrum in the treatment of shigellosis in children: a double‐blind, randomized, controlled trial

Abstract: Immunological approaches have been considered as an alternative therapeutic option for the treatment of enteric infections over the past few years. Hyperimmune bovine colostrum (HBC) is a potentially innovative immunological option in the management of shigellosis together with traditional antibiotic therapy. Children aged 1‐12 y with a history of bloody mucoid diarrhoea of less than 5 d duration were enrolled after their stool specimen was found to be positive for Shigella dysenteriae type 1 antigen by a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…dysenteriae infection were treated with 100 ml of hyperimmune colostral preparation against Sh. dysenteriae antigen I in combination with an antibiotic (pivmecillinam) three times per day for 3 days, no difference was found in any clinical parameter when compared with patients treated with control preparation and antibiotic (Ashraf, Mahalanabis, Mitra, Tzipori, & Fuchs, 2001). This suggests that in shigellosis the specific colostral antibodies can prevent the infection but are not effective in treatment of an already established one.…”
Section: Shigellamentioning
confidence: 92%
“…dysenteriae infection were treated with 100 ml of hyperimmune colostral preparation against Sh. dysenteriae antigen I in combination with an antibiotic (pivmecillinam) three times per day for 3 days, no difference was found in any clinical parameter when compared with patients treated with control preparation and antibiotic (Ashraf, Mahalanabis, Mitra, Tzipori, & Fuchs, 2001). This suggests that in shigellosis the specific colostral antibodies can prevent the infection but are not effective in treatment of an already established one.…”
Section: Shigellamentioning
confidence: 92%
“…The immunomodulatory effects of bovine colostrum have been described previously in both human and animal studies (Ashraf, Mahalanabis, Mitra, Tzipori, & Fuchs, 2001;Bolke et al, 2002;Boudry et al, 2007;Wei, Xu, Cheng, & Xiong, 2007). For example, some researchers have shown that bovine colostrum supplementation can improve immune parameters in highly trained cyclists (Shing et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…A well-known method of preventing diarrhea in neonatal calves is twice a day administration of surplus colostrum of the first and second milking mixed with milk or milk substitute throughout the period of the greatest risk of diarrhea, usually up to 10-12 days of life (Castrucci et al, 1984;Möstl and Bürki, 1988;Gutzwiller, 2002). Cow colostrum from nonimmunized cows or cows hyperimmunized with rotavirus, coronavirus, Escherichia coli or Shigella successfully prevents diarrhea also in neonates of other species (Brunser et al, 1992;Klobasa et al, 1994;Tzipori et al, 1994;Gomez et al, 1998;Ashraf et al, 2001;Shibata et al, 2001).…”
Section: Cow Colostrummentioning
confidence: 99%
“…The Ig additive in feed or in a milk-replacer (table 4) seems to be the most suitable for prophylaxis, whereas application in capsules or the administration of Ig concentrate is advisable in diarrhea therapy (Kelly et al, 1997;Graczyk et al, 1998Graczyk et al, , 1999Ashraf et al, 2001;He et al, 2001;Quigley et al, 2001;Solomon, 2002;Stefaniak et al, 2003Stefaniak et al, , 2004.…”
Section: Factors Affecting Protective Efficiency Of Orally Administermentioning
confidence: 99%